In Response to Modernity: A Study of Ten Minutes and 38 Seconds in this Strange World and Black Milk as Post-Postmodernist Texts - Huma Saeed (University of Chitral Journal of Linguistics and Literature, 2021)
The study explores the notion of ‘Modernity’ in the two texts Ten Minutes and 38 Seconds in This Strange World (2019) and Black Milk: On Motherhood and Writing (2007), written by British Turkish novelist Elif Shafak. Modernity contends German philosopher Jurgen Habermas is an ongoing process of rationalizing. In contradiction to the postmodern and post-structural theorists’ view that modernity has ended, Habermas argues it is an incomplete project initiated by scholars of Enlightenment. Moreover, Habermas contends that Postmodernism is a critique of modernity. The study views post-Postmodernism as a contemporary critical response to modernity. It analyses the role of modernity in steering the discourse of women and the outcasts of society to the center in the chosen texts. Modernity manifests itself in Shafak’s art of storytelling, as it aspires to bridge the cognitive and emotional gaps left by postmodern irony. The study delimits the vast notion of modernity to the exploration of two questions: Firstly, how does modernity help in bringing people close to each other by establishing relationships of friendship based on trust and sincerity? Secondly, what are the effects of modernity on women writers’ choice between their career and their motherhood responsibilities? in postmodern and post-postmodern times? The study seeks to open the research gamut for aspiring researchers to explore new avenues and a cosmopolitan space for tabooed and marginalized persons. Furthering the cause of providing a fecund ground for women who are self-reflexive and ready to respond to modernity in the rapidly changing present times.